Pituitary blastoma, expanding the spectrum of newly recognized entities. A case report - Meenakshi Swain; Sundaram Challa; Subodh Raju (Wolters Kluwer Medknow Publications, 2022)
Tumors of the pituitary gland and sellar region represent about 15% of all brain tumors, with pituitary adenoma being the commonest and pituitary carcinoma being very rare. Pituitary tumors in children are even rarer. Pituitary blastoma, a pediatric adenohypophysial tumor, is a new entity described in the 2017 WHO classification of pituitary tumors. This is a very rare tumor with only 21 cases reported so far. Hence, we are reporting this unusual case seen in a 7-month-old infant who presented with a large sellar/suprasellar mass with pressure symptoms of short duration. Typically, they present between 7-24 months of age. On histopathology, a cellular tumor was seen with primitive-looking round cells with scanty cytoplasm with few well-defined gland or rosette-like structures. The immunohistochemical stains showed diffuse strong staining for synaptophysin with a very high MIB-1 index. Other markers for common round cell tumors in this age group and hormonal markers of pituitary tumors were negative with INI-1 being intact. The initial cases described by Scheithauer presented with Cushing's disease and at least focally expressed adrenocorticotrophic hormone on immunohistochemistry. However, nonfunctioning tumors are also seen, albeit rarely. These are known to be associated with DICER 1 mutations and have a poor prognosis. Hence, morphologic recognition in the right clinical context and excluding other differential diagnoses in infants help make the correct diagnosis.